A discussion of inner south projection angle for performance analysis of dielectric compound parabolic concentrator - Yu, Xu; Su, Yuehong (Elsevier, 2015)
In the performance analysis of a trough compound parabolic concentrator (CPC), the concept of south projection angle is often used for the nonmeridional sunlight to compare with the acceptance angle of CPC to determine if solar radiation could be collected. The solar altitude and azimuth are the only two factors used to calculate the south projection angle. However, for the solid CPC made of dielectric material, due to the refraction on the air–dielectric interface, the optical path of refracted light within a dielectric CPC would also depend on the refractive index of dielectric material and the tilt angle of CPC. The conventional south projection angle would not be suitable for performance analysis of a solid dielectric CPC. This paper therefore introduces a concept of inner south projection angle which is based on the refracted light and derives a formula using vector analysis. The formula relates the inner south project angle with the solar altitude and azimuth, the refractive index, and the CPC tilt angle as well. Photopia software is meanwhile employed to predict the optical performance of dielectric CPC. The simulation results confirm that use of the inner south projection angle can determine if solar radiation could be collected or transmitted through a dielectric CPC rather than conventional south projection angle. Discussions are given about the correlation between the inner south projection angle and the optical efficiency and transmittance of a trough dielectric CPC. This provides a convenient way to evaluate the performance of a dielectric CPC over a period such as a whole year.